A study on the effects of Taijiquan learning for college students from the perspective of physical and mental cultivation - Du, Chengfeng; Du, Xiaohong; Zhu, Hongbo (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Taijiquan has a long history, extensive and profound, and is rich in Oriental culture with Chinese characteristics, covering the concepts of tuna guidance, health preservation, Taoist life and double cultivation. It is not only a martial art, but also a philosophy, a national spirit, a resource, and the ability to control one’s own energy. In 2020, Taijiquan officially became an intangible cultural heritage, which promoted the inheritance and development of taijiquan, set off a learning boom, and raised the importance of taijiquan to a certain height. Nowadays, there are many problems in taijiquan curriculum. It is urgent to seek new teaching methods and remobilize students’ interest in learning. Therefore, from the perspective of physical and mental cultivation, we discuss the psychological feelings and internal changes of students after learning Taijiquan after using the new teaching method, in order to inject new vitality into the teaching of Taijiquan course, make taijiquan more acceptable and easy to learn by college students, so as to promote the popularization and youth of Taijiquan. At present, most universities offer taijiquan course, but the teaching effect is not significant, even in the teaching of many problems. The present taijiquan teaching on the whole presents a strange phenomenon: most universities taijiquan courses belong to the homogenization of teaching, teaching process is to learn the movement posture; A small number of colleges and universities are struggling to carry out innovative teaching in the teaching process, but it is still difficult to pay attention to students’ proprioception in teaching. The general evaluation of taijiquan is that students move too slowly and too much, they are tired of remembering posture, and it is difficult to calm down to learn, and they cannot judge their own proprioception. Teachers use the unchanged teaching method of spoon-feeding teaching, and tell too little about the profound connotation of traditional culture, making students lack interest and correct guidance to explore themselves. Moreover, college students generally have problems such as great learning pressure, physical and mental separation, anxiety, etc. , which have not been well paid attention to and solved, so it is difficult to pay attention when learning movements, and it is more difficult to meditate to explore their own feelings. Studies have shown that Tai Chi has a significant regulating effect on the human body. We should make use of the advantages of Tai Chi and innovative teaching mode to reintroduce Tai Chi into the curriculum, so as to solve the problems such as poor teaching effect and students’ inability to devote themselves to learning. Methods: In view of this kind of problem, this paper conducts an in-depth study on the teaching effect of taijiquan course in colleges and universities by using the methods of literature, logical analysis and experiment. The experimental method recruited 60 subjects from a school and randomly divided them into the experimental group and the control group. The experimental time was 90 minutes. The control group sat quietly for 15 minutes, and the experimental group first received a brief training on the core techniques of Tai Chi, and then followed the innovative teaching video of Tai Chi for 15 minutes. In addition, the internal sensitivity Scale (MAIA) and five factor Mindfulness Scale (FFMQ) and computer image recognition button operation were also required. Results: When the core techniques of Taijiquan were refined and coordinated with the breathing and the shift of center of gravity, the subjects could get into the state quickly. When the subjects conducted video learning, the uniform ups and downs of breathing and heart rate were observed through the breathing band to confirm the subjects’ practicing state of Tai Chi. There was a significant difference in unhappiness score between the experimental group (P = 0. 027). There was a significant difference between pretest and posttest MAIA score in the experimental group (P < 0. 001). Internal receptivity Scale (MAIA); The change of MAIA (protest-pretest) was significantly different between the experimental group and the control group (P < 0. 001). There was significant difference in FFMQ score between the experimental group in pretest and protest (P < 0. 001); Five-factor Mindfulness Scale (FFMQ); There was significant difference between the experimental group and the control group in the change of FFMQ(pretest-pretest) (P < 0. 001); The above results show that taijiquan practice has significant changes in internal sensitivity and mindfulness, indicating that the changes in taijiquan teaching methods can affect students’ learning state and physical and mental state, and can effectively regulate students’ negative emotions, so that students can better relax their bodies and achieve the situation of both life and learning. Conclusion: Through the experiment, it is concluded that the innovative taijiquan teaching has significant effects on students’ inner sensitivity, attention, individual emotions, pressure relief and other aspects. The effect of taijiquan pile relaxation practice is particularly important, making students feel the real feeling of calm and loose body. Through the push and pull experience, students can quickly grasp the coordination and order of strength of upper and lower limbs, focusing on the essence of taijiquan. The core of this new teaching process is to make students fully clear from the nature and movement pattern: Tai Chi is a relatively static and slow push and pull, and the practitioner needs to gradually form a sense of goal in the process of movement. At the same time, let college students in the process of learning Tai Chi to dig their own internal feelings of the body, and then experience tai Chi for the body and mind of the real value of mind and fitness. In the process of practice, the body and mind can be relaxed, which makes the brain more sensitive. The personal experience of relaxation can strengthen the proprioception of students. In addition, the new teaching method can make students consciously distinguish their own action norms, which can effectively improve the subjective initiative of students in learning. It can be seen that the practice of body-mind tai Chi is not a simple way to learn boxing, but a steadfast way to cultivate the mind. In the future teaching process, continuous feedback on teaching and learn.